Business Opportunity: Card Capital / Muhammad Haikal Mohd Asmawi - Mohd Asmawi, Muhammad Haikal (2021)
In this era of globalization, it is undeniable that business play an important role in the economic development of the nation and for the upliftment of living standard of the people. Without business, nations' economies would be much smaller and weaker than they are. Therefore, there are several of business being proposed and carried out among our society in order to keep the growth of economy. For this report, I will be covering on a business on a game shop called Card Capital. As for the reason it was called by that name is because for starters just by saying the shops name it can attract some customers interest in stopping by to check out the shop. The shops name is also not utterly short nor is it ridiculously long, its just a short and basic name to be memorable and easier for the customer to remember. The store is located at a nearby residential area which happens to be near a school. The reason for the store being located there is because can be a main factor in attracting future customers which the target customers for the shop being students that would be interested in the games that is sold at the store. Plus, our store provides a place for the customers to play their games with their fellow friends, the store also host weekly events that can encourage the children at the nearby residential area to come and play the games they love at the shop while the shop provided prizes that can further encourage the customers to frequently come to the shop and build a good community in the shop.